2020
DOI: 10.1155/2020/9598210
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Tamponade Caused by Cutibacterium acnes: An Updated and Comprehensive Review of the Literature

Abstract: Bacterial pericarditis is a critical diagnosis caused by a wide range of organisms including Streptococcus pneumoniae and other anaerobic organisms like Cutibacterium acnes which has been gaining more importance as a causative organism. Cutibacterium species are Gram-positive microaerophilic rods that constitute part of the normal flora of skin and mucosal membranes. The incidence of pericarditis caused by this organism is underreported as it is often dismissed as a skin flora contaminant. However, if left unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…(2020) reported that Pantoea was closely related to bacteremia in humans. Cutibacterium was considered as skin flora contaminant, which can result in pericarditis with serious complications ( Fakhri et al., 2020 ). Moreover, Cutibacterium was also closely related to multiple postoperative complications, including persistent postoperative pain, chronic inflammation, and endoprosthesis involving bacterial biofilms because it ubiquitously colonizes the skin and resides in various other locations in the human body ( Patel et al., 2009 ; Achermann et al., 2013 ; Hudek et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2020) reported that Pantoea was closely related to bacteremia in humans. Cutibacterium was considered as skin flora contaminant, which can result in pericarditis with serious complications ( Fakhri et al., 2020 ). Moreover, Cutibacterium was also closely related to multiple postoperative complications, including persistent postoperative pain, chronic inflammation, and endoprosthesis involving bacterial biofilms because it ubiquitously colonizes the skin and resides in various other locations in the human body ( Patel et al., 2009 ; Achermann et al., 2013 ; Hudek et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier review of the literature between 1889 and 1975, Klacsmann et al found Streptococcus pneumoniae as the prevalent bacterial cause of infectious pericarditis prior to 1943 and Staphylococcus aureus as the most prevalent after 1943 [4]. However, according to recent data, Cutibacterium acnes, formerly, Propionibacterium acnes, appears to play an important role as a causative agent of pericarditis [1,3,[5][6][7][8]. In a retrospective study done at Mayo Clinic, the three frequently identified causes of bacterial pericarditis were C. acnes, Staphylococci spp, and Streptococci spp, with C. acnes being the most prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious pericarditis presents a diagnostic challenge in an immunocompromised patient due to poor inflammatory response. In this scenario, fever, pleuritic chest pain, and frictional rub may be missing [ 1 , 2 ]. The most common cause of infectious pericarditis is viral.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations